Forms of English Learning and Teaching Interactions In an International Oriented Senior High School - Chairani, Noor (Ahmad Dahlan Journal of English Studies, 2015)
AbstractIn English learning and teaching process, interaction between participants plays important roles to take and give inputs that emphasizes on the activeness of learners in acquiring the target language. Learners will be more autonomous, self-actualized and self-fulfilled when in learning and teaching process involves them. Interaction can be implemented by teacherâs treatment to learners and learnersâ to themselves. Hence, learner will cope with their reality of the world and win their competition to exist confidently in the world using English used by people in the world as one of international languages.This research was on English learning and teaching interaction in an international oriented senior high school conducted to generate the forms of English learning and teaching interaction at the school. The data collection in this research used interviews and classroom observations at the school. The interviews and classroom observations were recorded and then transcribed into written data. The data were analyzed and coded into concepts, subcategories and category which were related to each other. The research was qualitative study and using the grounded theory approach. The participants in this research were divided into five categories: a deputy principal of curriculum, two English teachers, a content course teacher, a tutor and twelve learners at SMA Internasional Budi Mulia Dua Yogyakarta especially at GAC classes that use ACT curriculum. It covered many data texts included from observations and interviews to get understanding deeply between the theories and the practical things in the school. From the data analysis, there are three forms of interaction which occurred in the English learning and teaching interaction between learner and teacher, between learner and learner and between learner and people outside of school.